2017
DOI: 10.1177/0969733017727155
|View full text |Cite
|
Sign up to set email alerts
|

Academic ethical awareness among undergraduate nursing students

Abstract: Personal behaviors were rated with low ethical awareness in relative, but items related to public rules and actual effects on patients or others were rated with higher score. Nursing satisfaction and academic stress are main factors on ethical awareness. To improve overall ethical awareness level of nursing students, it is required to provide more education about the importance of personal behaviors in class and need to improve the understanding of how it will be connected with future situation and effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 20 publications
(37 reference statements)
5
21
0
1
Order By: Relevance
“…Students might become more emotional and sensitive to ethical issues and dilemmas that they learned in their lectures. Consistent with this result, Choi (2019) and Cho and Hwang (2019) established that moral sensitivity was negatively correlated with school years, whereas moral sensitivity decreased with advance in study years. In contrast, M. Park et al (2012) found that senior nursing students had greater moral sensitivity than freshman students.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Students might become more emotional and sensitive to ethical issues and dilemmas that they learned in their lectures. Consistent with this result, Choi (2019) and Cho and Hwang (2019) established that moral sensitivity was negatively correlated with school years, whereas moral sensitivity decreased with advance in study years. In contrast, M. Park et al (2012) found that senior nursing students had greater moral sensitivity than freshman students.…”
Section: Discussionsupporting
confidence: 67%
“…Academic ethics requires students to be conscientious, rational, have a good sense of duty to avoid unsuitable learning habits/manners, and strive for academic excellence ( Cho & Hwang, 2019 ). Academic Ethical Awareness (AEA) aims to understand academic values and maintain the proper attitude to guide all learning activities.…”
Section: Review Of Literaturementioning
confidence: 99%
“…According to the results, the frequency of clinical dishonesty was related to being interested in nursing; thus, the frequency of these behaviors in students who were "interested" and "somewhat interested" was less than that of those who were "uninterested". Also, a study found that students who were satisfied with nursing were likely to have higher ethical awareness, be more faithful to their discipline and its ethics, and exhibit less dishonest behaviors [21]. In Iran, most students typically choose their field of study based on their scores on the Iranian University Entrance Exam (IUEE).…”
Section: Discussionmentioning
confidence: 99%
“…According to the results, the frequency of clinical dishonesty was related to being interested in nursing; thus, the frequency of these behaviors in students who chose "interested" and "somewhat interested" was less than of those who chose "uninterested". Also, a study found that students who were satisfied with nursing were likely to have higher ethical awareness, be more faithful to their discipline and its ethics, and exhibit less dishonest behaviors [21]. In Iran, students choose their field of study based on their scores on the National Entrance Exam.…”
Section: Discussionmentioning
confidence: 99%